The clinical auditor's perspective: to err is human - Jasperse, Dorcie McKniff, author; Society of Quality Assurance, publisher (Colorado State University. Libraries, 2016)
Accelerated by technology, our pharmaceutical, biotechnology and medical device industries are changing at the speed of light. With these technological changes, some management personnel seem to believe that if processes are controlled by technology, lesser qualified personnel can fill many roles in the clinical trials. In some companies, this leads to a dangerous disconnect where technology improves, but the quality of the personnel diminishes and data integrity is therefore put at risk. Compounding this trend is a misplaced trust in robots and computers, and insufficient numbers of personnel to grow into the shoes of retiring seasoned veterans. In this session several examples will be provided where the most basic of human errors go undetected by personnel in clinical trials; errors that were not or could not be detected by electronic systems used to ensure data integrity. Several other examples will be provided from the aerospace and the healthcare industry. In our industry, human creativity and ingenuity abound and should flourish, however it is incumbent on all champions of quality to ensure that the source of data integrity is recognized as: • The result of well-developed technical prowess as well as a well-developed workforce armed with basic and fundamental stewardship skills and • An awareness and integration of the larger view, combined with an eye for detail to establish a solid foundation for data integrity across any situation or platform. We will provide perspectives and suggestions to address this challenging situation, helping to ensure clinical data integrity vital for FDA decision making.
Presented at the National data integrity conference: data sharing: the how, why, when and when not to share held on June 2-3, 2016 at University of Colorado, Denver, Colorado. The National Data Integrity Conference is a gathering of people sharing new challenges and solutions regarding research data and integrity. This conference aims to provide attendees with both an understanding of data integrity issues and impart practical tools and skills to deal with them. Topics addressed will include data privacy, openness, policy, education and the impacts of sharing data, how to do it, when to do it, and when not to. Speakers and audience members come from diverse fields such as: Academic Research; Information Technology; Quality Assurance; Regulatory Compliance; Private Industry; Grant Funding; Government.
PowerPoint presentation during Lightning Talks given on June 3, 2016.
Dorcie is affiliated with Raland Compliance Partners.
Keywords: computer trust; misguided computer trust; data; analysis; electronic data capture; clinical auditing